1999
DOI: 10.1046/j.1365-2273.1999.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Admission rates, early readmission rates and patient acceptability of 142 cases of day case septoplasty

Abstract: Day case surgery should be confined to those procedures where less than 3% of patients require admission. The aim of this study was to establish the admission rates, early readmission rates and patient acceptability of 142 consecutive cases of day case septoplasty. Data acquisition was by retrospective postal questionnaire. One hundred and fifty-three patients were studied and data was acquired on 142. Ninety per cent (128/142) of patients had operations on afternoon lists. Admissions were 7/142 (5%), the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 5 publications
1
28
0
1
Order By: Relevance
“…7,8 The use of local anesthetics and vasoconstrictors in rhinoseptoplasty surgery is well known. Hogg et al 1 reported the following treatment: First the nose should be prepared with xylometazoline 0.1% spray. Next, the septum should be infiltrated before surgery with 4 ml of 0.2% lidocaine with 1:80,000 epinephrine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 The use of local anesthetics and vasoconstrictors in rhinoseptoplasty surgery is well known. Hogg et al 1 reported the following treatment: First the nose should be prepared with xylometazoline 0.1% spray. Next, the septum should be infiltrated before surgery with 4 ml of 0.2% lidocaine with 1:80,000 epinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…Résultats L'application de lidocaı¨ne-naphazoline intranasale a diminue´les besoins en isoflurane [valeurs me´dianes : 0,8% (0,7-1,5) vs 1,2% (0, 8) Septorhinoplasty is generally considered to be a traumatic procedure associated with epistaxis, periorbital hematoma, and postoperative pain. 1 The leading causes of hospital readmission and/or overstay after day-care septorhinoplasty surgery are epistaxis and a high level of postoperative pain. 2 A multimodal analgesia regimen can be used, but many patients suffer from adverse events after opioid administration.…”
Section: Résumémentioning
confidence: 99%
“…On the other hand, there are more studies available than for antrostomy. Several older studies drew conflicting conclusions regarding day-case management of septoplasty, due to readmission rates that varied from 2% to 13.4% [27][28][29][30][31].…”
Section: Guideline 14mentioning
confidence: 99%
“…Les études sont par contre plus abondantes que pour les méatotomies moyennes. Plusieurs études anciennes ont tiré des conclusions contradictoires concernant la prise en charge des septoplasties en ambulatoire en raison de taux de réadmission variant de 2 à 13,4 % [27][28][29][30][31].…”
Section: Recommandation 14unclassified